Gestión de atención a clientes en empresas de servicios de salud ocupacional - Parra Franco, Enma Maribel (2023)
This research work focuses on the analysis of Customer Service Management in Occupational Health Services Companies; In most cases, customer service is not used in a structured way in the different areas of the organization, which is why the implementation of a customer service culture model is appropriate. In Chapter I, the approach to the problem of Occupational Health Services Companies is described, with regard to customer service. The formulation of the problem, the research questions, the general objective, the specific objectives, the justification, the ideas to defend and the study variables are presented...........